Transient abnormal myelopoiesis with pericardial effusion in Down syndrome: Case report - Falasco, Bianca Francisco (Clin Case Rep, 2019)
Pericardial effusion associated with transient abnormal myelopoiesis in Down's syndrome neonates needs to be diagnosed in a timely manner, and the comorbidities must be treated to prevent mortality. To our knowledge, the occurrence of basophilic/eosinophilic pericardial effusion without an increase of these cells in the peripheral blood and with no evidence of associated hypothyroidism is rare.